Blockchain Governance Models for Enhancing E-Commerce User Satisfaction - Bangun, Cicilia Sriliasta Bangun; Riskhandini, Dinda Putri ; Lyraa , Naomi (IAIC Bangun Bangsa, 2025)
Blockchain technology has emerged as a transformative innovation in various sectors, including e-commerce. Effective blockchain governance plays a pivotal role in enhancing user satisfaction by ensuring security, transparency, and efficiency in online transactions. However, despite its growing adoption, many e-commerce platforms face challenges in implementing governance models that fully address user expectations and technological complexities, revealing a significant gap in the literature. This study investigates the impact of blockchain governance models on e-commerce user satisfaction, with a specific focus on mediating variables such as data privacy and system trust, and moderating variables such as user technology readiness. The study employs the Structural Equation Modeling (SEM) method using SmartPLS software to analyze relationships between variables. Data was collected through a survey of 135 respondents, consisting of e-commerce users familiar with blockchain technology. The Result reveals that blockchain governance significantly impacts data privacy and system trust, which, in turn, influence perceived ease of use and user satisfaction. Additionally, user technology readiness moderates the relationship between blockchain governance and perceived ease of use, highlighting its importance in adoption. The Novelty of this study lies in its integration of governance frameworks with mediating and moderating variables to holisticallyaddress e-commerce user satisfaction, an area underexplored in prior research. The conclusion emphasizes the need for e-commerce platforms to adopt robust blockchain governance frameworks to improve user satisfaction and gain a competitive advantage. This study contributes to the literature on blockchain applications in e-commerce and provides practical recommendations for enhancing governance and user experience.